Derivation of Criterion Suitable for Evaluation of Multichannel Noise Reduction Systems for Speech Processing - P. Sovka (Radioengineering, 2009)
This paper deals with the theoretical derivation of the Noise Reduction criterion suitable for evaluation of multichannel noise reduction system performance. This criterion is suitable for noise suppression assessment and thus serves as an important step in the development of noise reduction systems. Noise reduction is evaluated in dependence on spatial coherence. The derivations are made for ﬁve basic multichannel systems, Delay and sum beamformer, Beamformer with adaptive postprocessing, Generalized sidelobe canceller, Linearly constrained beamformer, and Modiﬁed coherence ﬁlter.